Pengendalian Air Limpasan dengan Ecodrainage untuk Kawasan Perumahan Podo Asih - Setiawan, Arifandy; Yulistyorini, Anie; Rahayuningsih, Titi; Idfi, Gilang (Universitas Andalas, 2023)
Podo Asih Housing is a residential area located in Beji District, Pasuruan Regency, located at 7Â°34'23.21â€ S and 112Â°44'00.39â€ E housing area of 50,000 m2 or 5 hectares, this relatively densely populated housing is still frequent. There is a flood that can disrupt the activities of residential residents. One alternative to overcome this is by applying the concept of eco-drainage in residential areas. This study uses a quantitative descriptive approach to the Podo Asih Housing area, hydrological analysis is carried out to determine runoff discharge and hydraulic analysis to determine the capacity of the existing channel in the Podo Asih Housing area, the analysis is carried out to determine how much runoff discharge occurs, that is the basis In eco-drainage planning, it is necessary to take into account how many rainwater reservoirs, infiltration wells, and biopore infiltration holes are needed to control the runoff water. In collecting data, researchers conducted observations and measurements directly in the field, carried out laboratory tests, and collected rain data from the Department of Irrigation and Mining of Pasuruan Regency. HEC-RAS software for hydraulic analysis calibration. The results showed that there were 39 out of 118 channels that could not accommodate runoff water discharge, planned as many as 378 rainwater collectors, 68 infiltration wells, and 289 biopore infiltration holes that could reduce runoff discharge by 1,253 m3/s with a reduction percentage of 95.59% for a 2 year return period, 77.06% for a 5 year return period, and 68.19% for a 10 year return period.Â Keywords: housing, runoff, ecodrainageÂ Â ABSTRAKÂ Perumahan Podo Asih merupakan kawasan perumahan yang terletak di Kecamatan Beji Kabupaten Pasuruan, terletak pada 7Â°34'23.21â€ LS dan 112Â°44'00.39â€ BT dengan luas perumahan 50.000 m2 atau 5 hektar, perumahan yang relatif padat penduduk ini masih sering dijumpai. Adanya banjir yang dapat mengganggu aktivitas warga pemukiman. Salah satu alternatif untuk mengatasi hal tersebut adalah dengan menerapkan konsep ecodrainage pada kawasan pemukiman. Penelitian ini menggunakan pendekatan deskriptif kuantitatif pada kawasan Perumahan Podo Asih, analisis hidrologi dilakukan untuk menentukan debit limpasan dan analisis hidrolik untuk mengetahui kapasitas saluran yang ada di kawasan Perumahan Podo Asih, analisis dilakukan untuk mengetahui seberapa besar terjadi debit limpasan, yang menjadi dasar Dalam perencanaan ekodrainase, perlu diperhitungkan berapa jumlah penampungan air hujan, sumur resapan, dan lubang resapan biopori yang dibutuhkan untuk mengendalikan air limpasan. Dalam pengumpulan data, peneliti melakukan observasi dan pengukuran langsung di lapangan, melakukan uji laboratorium, dan mengumpulkan data hujan dari Dinas Pengairan dan Pertambangan Kabupaten Pasuruan. Perangkat lunak HEC-RAS untuk kalibrasi analisis hidrolik. Hasil penelitian menunjukkan terdapat 39 dari 118 saluran yang tidak dapat menampung debit air limpasan, direncanakan sebanyak 378 penampung air hujan, 68 sumur resapan, dan 289 lubang resapan biopori yang dapat mereduksi debit limpasan sebesar 1.253 m3/s dengan persentase penurunan. sebesar 95,59% untuk periode ulang 2 tahun, 77,06% untuk periode ulang 5 tahun, dan 68,19% untuk periode ulang 10 tahun.Â Kata kunci: perumahan, limpasan, ekodrainaseÂ Â Â Â Â Â